IMPROVEMENT OF MARKETING PERFORMANCE BASED ON PRODUCT INNOVATIVENESS - Mulyanto, Kukuh; Firdaus, Firdaus (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2020)
The dynamics of business competition is very strict demands that businesses must have a good marketing performance to be able to compete with competitors. One strategy that can be used by businesses to improve marketing performance. Marketing a good performance will facilitate the success of a business, in this case the performance marketing is seen as the spearhead of success in achieving corporate goals for future. The purpose of this research is done in order to investigate the variable product innovativeness, towards differentiation advantage and cost advantage to improve the marketing performance of SMEs in Semarang. This data research using questionnaires. The sampling technique is to use probability sampling, with one of the methods used is purposive sampling.